Twin cities: a new form of cross-border cooperation in the Baltic Sea Region? - Anishenko, Anatoly G.; Sergunin, Alexander (Baltic Region, 2013)
The paper demonstrates the first attempt in Russian political studies to conduct a comprehensive analysis of the "twin city" movement as a form of cross-border cooperation in the Baltic region. This phenomenon emerged as a result of a global tendency towards more active involvement of municipal units in international cooperation, on the one hand, and aspirations of frontier cities and towns in the Baltic region to solve common problems together, on the other hand. This work is based on a comparative analysis method and a case study methodology. The authors consider four examples (city pairs): Tornio - Haparanda, Valga - Valka, Narva - Ivangorod and Imatra - Svetogorsk. The article specifies the terminological framework used in this field of research. The authors analyse achievements and failures of this type of international inter-municipal cooperation and emphasise that for twin cities it served not only as a means of survival in the difficult situation of the 1990s, but also as an experimental ground for new forms of crossborder cooperation. The authors arrive at the conclusion that this model proves to be promising for further development of integration processes in the Baltic region. This practice can be applied by Russian municipal, regional and federal authorities in promotion of cross-border cooperation not only in the Baltic region, but also in other regions of the country. Thus, influenced by the successful experience of Baltic frontier cities and towns, the Russian city of Nikel and the Norwegian city of Kirkenes decided to adopt this model for further development of their cooperation.